Factors Affecting the Intention to Use Electronic Banking Services Via Mobile Phone in Iraq and Solutions to Improve Them (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
The development of the situation in the banking sector led to an increase in competition in providing distinguished electronic banking services to customers, which prompted banks to explore the factors influencing customers' intention to use electronic banking services through mobile phones in Iraqi banks and to provide solutions thereto. The problems that Iraqi banks suffer from. Where the research problem was represented in the lack of use of telephone banking services, although they are available 24 hours a day. Therefore, the importance of the research stems from studying the impact of electronic banking services of Iraqi banks over the phone and its impact on the intention to use customers.The research relied on a basic hypothesis that the security of mobile banking services greatly affects the customers' intention to use them. The researcher used the analytical descriptive approach, where the research community represented all users of electronic banking services for banks (Ravidian - Al-Rashid Commercial), where a cluster sample was drawn Consisting of (120) clients. The researcher used a questionnaire form consisting of (30) items, in which the opinions of bank customers were surveyed about what they actually receive from mobile banking services. He also used SPSS. He performed T and Anova tests to show the influence of demographic factors, and analyzed the standard deviation and the arithmetic mean.Among the most important findings of the researcher is that there is an effect of demographic variables on the use of mobile banking services, and that the use of this service reduces transportation costs, and the highest component is the mean (4.03) and the deviation (0.90), which means that there is an agreement to use the service that facilitates In carrying out banking tasks and reduces the costs incurred by the customer